Performance evaluation of palm oil-based biodiesel combustion in an oil burner - Ganjehkaviri, Abdolsaeid (MDPI AG, 2016)
This paper presents an experimental investigation of the combustion characteristics of palm methyl ester (PME), also known as palm oil-based biodiesel, in an oil burner system. The performance of conventional diesel fuel (CDF) and various percentages of diesel blended with palm oil-based biodiesel is also studied to evaluate their performance. The performance of the various fuels is evaluated based on the temperature profile of the combustor's wall and emissions, such as nitrogen oxides (NOx) and carbon monoxide (CO). The combustion experiments were conducted using three different oil burner nozzles (1.25, 1.50 and 1.75 USgal/h) under lean (equivalence ratio (φ) = 0.8), stoichiometric (φ = 1) and rich fuel (φ = 1.2) ratio conditions. The results show that the rate of emission formation decreases as the volume percent of palm biodiesel in a blend increases. PME combustion tests present a lower temperature inside the chamber compared to CDF combustion. High rates of NOx formation occur under lean mixture conditions with the presence of high nitrogen and sufficient temperature, whereas high CO occurs for rich mixtures with low oxygen presence.